Targeted Proteomics Approach Toward Understanding the Role of the Mitochondrial Protease FTSH4 in the Biogenesis of OXPHOS During Arabidopsis Seed Germination - Heidorn-Czarna, Malgorzata; Domanski, Dominik; Kwasniak-Owczarek, Malgorzata; Janska, Hanna (Frontiers in Plant Science, 2018)
Seed germination provides an excellent model to study the process of mitochondrial biogenesis. It is a complex and strictly regulated process which requires a proper biogenesis of fully active organelles from existing promitochondrial structures. We have previously reported that the lack of the inner mitochondrial membrane protease FTSH4 delayed Arabidopsis seed germination. Here, we implemented a targeted mass spectrometry-based approach, Multiple Reaction Monitoring (MRM), with stable-isotope-labeled standard peptides for increased sensitivity, to quantify mitochondrial proteins in dry and germinating wild-type and ftsh4 mutant seeds, lacking the FTSH4 protease. Using total seed protein extracts we measured the abundance of the peptide targets belonging to the OXPHOS complexes, AOX1A, transport, and inner membrane scaffold as well as mitochondrial proteins that are highly specific to dry and germinating seeds. The MRM assay showed that the abundance of these proteins in ftsh4 did not differ substantially from that observed in wild-type at the level of dry seed and after stratification, but we observed a reduction in protein abundance in most of the examined OXPHOS subunits in the later stages of germination. These changes in OXPHOS protein levels in ftsh4 mutants were accompanied by a lower cytochrome pathway activity as well as an increased AOX1A amount at the transcript and protein level and alternative pathway activity. The analyses of the steady-state transcript levels of mitochondrial and nuclear genes encoding OXPHOS subunits did not show significant difference in their amount, indicating that the observed changes in the OXPHOS occurred at the post-transcriptional level. At the time when ftsh4 seeds were fully germinated, the abundance of the OXPHOS proteins in the mutant was either slightly lowered or comparable to these amounts in wild-type seeds at the similar developmental stage. By the implementation of an integrative approach combining targeted proteomics, quantitative transcriptomics, and physiological studies we have shown that the FTSH4 protease has an important role in the biogenesis of OXPHOS and thus biogenesis of mitochondria during germination of Arabidopsis seeds.